Measurement of Individual H+ and O+ Ion Temperatures in the Topside Ionosphere. Issue 2 (14th February 2018) - Hsu, Chih‐Te; Heelis, Roderick A.
Abstract: Plasma temperatures in the ionosphere are associated with both the dynamics and spatial distribution of the neutral and charge particles. During the daytime, temperatures are determined by solar energy inputs and energy exchange between charged and neutral particles. Plasma transport parallel to the magnetic field adds another influence on temperatures through adiabatic processes that are most evident during the nighttime. Previous observations suggest that the topside H + temperature ( T H+ ) should reside between the O + temperature ( T O+ ) and the electron temperature ( T e ), and further calculations confirm the preferential heat transfer from the electrons to H + in the topside. In this work we implement a more sophisticated analysis procedure to extract individual mass‐dependent ion temperatures from the retarding potential analyzer measurements on the DMSP F15 satellite. The results show that the daytime T H+ is a few hundred degrees higher than T O+ at all longitudes. The nighttime temperature difference between T H+ and T O+ is indicative of mass‐dependent adiabatic heating and cooling processes across the equatorial region. The ion temperatures and measured plasma flows present clear longitudinal variations that are associated with magnetic declination. Key Points: A more sophisticated analysis procedure to extract O + and H + temperatures ( T O+ and T H+ ) from RPA was implemented When electrons are heated during daytime, T O+ < T H+ When O + is adiabatically heated at night, T O+ > T H+